Latest Maastrichtian middle- and high-latitude mosasaurs and fish isotopic composition: carbon source, thermoregulation strategy, and thermal latitudinal gradient - Leuzinger, Léa Sylvia; Kocsis, László; Luz, Zoneibe; Vennemann, Torsten Walter; Ulyanov, Alexey; Fernández, Marta Susana (Paleobiology)
Here we report high-latitude stable isotope compositions of Maastrichtian fossil fish and marine reptiles (mainly mosasaurs) from Antarctica (64°S paleolatitude) and compare them with mid-paleolatitude samples from Argentine Patagonia (45°S). Disparities between the δ13C values of bony fish and marine reptiles correspond to differences in the foraging ground (distance from the shore and depth), while dramatically higher δ13C values (by 18‰) in shark enameloid cannot be explained through ecology and are here imputed to biomineralization. Comparison with extant vertebrates suggests that the diet alone can explain the offset observed between bony fish and mosasaurs; however, breath holding due to a diving behavior in mosasaurs may have had some impact on their δ13C values, as previously suggested. The δ18OPO4 values of the remains confirm a relatively stable, elevated body temperature for marine reptiles, meaning that they were thermoregulators. We calculated a water temperature of ~8°C for Antarctica from the fish δ18OPO4 values, warmer than present-day temperatures and consistent with the absence of polar ice sheets during the latest Maastrichtian. Our fish data greatly extend the latitudinal range of Late Cretaceous fish δ18OPO4 values and result in a thermal gradient of 0.4°C/1° of latitude when combined with literature data. Fil: Leuzinger, Léa Sylvia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Kocsis, László. Universite de Lausanne; Suiza Fil: Luz, Zoneibe. Universite de Lausanne; Suiza Fil: Vennemann, Torsten Walter. Universite de Lausanne; Suiza Fil: Ulyanov, Alexey. Universite de Lausanne; Suiza Fil: Fernández, Marta Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; ...